Suicide deaths following police contact: A review of coronial inquest findings. Issue 3 (16th March 2022) - Chidgey, Kelly; Procter, Nicholas; Baker, Amy; Grech, Carol
Abstract: We analyzed 10 years of Australian coronial inquest documents on people who died by suicide or suspected suicide following recent contact with the police. We identified 149 cases of suicide or suspected suicides via coronial websites, 34 of which contained recommendations. We developed four themes from these recommendations, the most common of which was for police to change current practices or policies and modify police officer training. Coroners considered effective working relationships with external stakeholders able to assist police an important means of reducing risk of suicide.